MEDICINAL CORRECTION OF CATALASE ACTIVITY AND SUPEROXIDE DISMUTASE IN PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS - Худякова М. Б. (World of Medicine and Biology, 2015)
The analysis proves pathogenetic role of abnormal processes of antioxidant defense in the oral fluids in their connection with clinical change in development of chronic generalized periodontitis of I-II degrees of severity. The scheme of complex treatment of periodontitis by means of local application of lipoflavon (liposomal quercetin-lecithin complex) using individual periodontal polyvinylchloride delivery tray contributing to inflammation elimination and long-term remission has been developed. This allows to recommend lipoflavon for local application as pathogenetically antioxidant substantiated drug in treatment of generalized periodontitis.